(untitled) (The Review of Diabetic Studies, 2025)
Background: Appendectomy is one of the most frequently performed emergency surgical procedures, with laparoscopic and open techniques being the main approaches for treating acute appendicitis. Postoperative complications remain an important concern, as they affect patient recovery, length of hospital stay, and healthcare costs. Comparing complication prevalence between laparoscopic and open appendectomy is essential for optimizing surgical outcomes and guiding clinical practice. Methods: A retrospective cross-sectional study was conducted using medical records of patients who underwent laparoscopic or open appendectomy for acute appendicitis. Demographic characteristics, surgical approach, and postoperative complications were collected and analyzed. The primary outcome was the prevalence of postoperative complications, including surgical site infection, intra-abdominal abscess, postoperative ileus, and bleeding. Data were analyzed using descriptive statistics and presented as frequencies and percentages. Results: A total of 200 patients were included in the study, with 120 undergoing laparoscopic appendectomy and 80 undergoing open appendectomy. The overall prevalence of postoperative complications was 28.0%. Complications occurred in 20.0% of patients who underwent laparoscopic appendectomy compared with 40.0% of those who underwent open appendectomy. Surgical site infection was the most common complication in both groups, with a notably higher frequency observed following open appendectomy. Conclusion: Laparoscopic appendectomy was associated with a lower prevalence of postoperative complications compared with open appendectomy. These findings support the use of laparoscopic appendectomy, when feasible, as a preferred surgical approach to reduce postoperative morbidity in patients with acute appendicitis.